Real Wages in Canada 1919-1932 With A Special Analysis of Earnings in 1931 - Royall, W H. (My University, 2011)
In In recent times, such phrases as, "Standard of Living" and "Purchasing Power", are on everybody's lips. And yet these everyday expressions have no intelligible meaning for many people. We find that in trying to clarify the concept of real wages, we soon get into enough statistical difficulties, to render the conclusion less positive than we had hoped, would result.
We have attempted our study in the following order. First: An historical review of real wages in Canada, obtained from wage rates, weighted with the cost of living and adjusted for unemployment. Second: An analysis of "Earnings Among Wage-Earners in Canada", as published by the Dominion Bureau of Statistics in Bulletin No. 33 of the census of 1931. Third: An attempt is made to relate these earnings to representative budgets for that year.
Keywords: Political Economy; Political Economy